Virtual service migration based on fuzzy logic approach - Zihou WANG; Yuemei XU; Luchen ZHANG (Dianxin kexue)
During the lifetime of virtual network, users' requirements for virtual services will be affected by their locations, behaviors and mobility. For a green, energy-saving, efficient-using virtual resource migration and scheduling, the service migration method based on fuzzy logic inference was proposed. The method could infer the changes of user demand, migrate the virtual service according to the changes. It would increase the resource utilization and the QoE.